Online Grammar Learning of Students in Bachelor of English Literature Program: A Focus on How the Learners Perceive Their Improvement - Ly Sovann; Dy Dalin; Mork Vichetsreypich; Sokun Vannthida; Touch Sonaryroth (Journal of English for Specific Purposes in Indonesia, 2024)
Online grammar is a popular way for students to improve their language skills through digital resources, such as websites, apps, and online courses. However, the study on online learning grammar has not been found in the research context and location. This study investigates how students learn grammar online, how they perceive the improvement and to find out activities that students apply to cross-check the improvement of their online grammar learning. The data was collected through survey questionnaires and face-to-face interviews. By using mixed methods, the questionnaire survey was created through Google Forms and collected from 108 participants of EFL students. The last instruments were interviews to find out more about the improvement of students in online grammar learning. The researchers selected 24 participants randomly from year 2, 3, and 4 students in English Literature of the Institute of Foreign Languages to interview about their perceptions of the improvement of such learning methods. The result showed that 82.4% of students stated that online grammar has improved their understanding of complex grammar concepts and increased their confidence in using English language grammar. And 80.60% agreed with the statement that online grammar learning has increased their ability to English language. Another 77.8% agreed that online grammar learning has improved their ability to construct persuasive arguments in writing. These findings show that it’s really important to know about what ways or activities that each student use to learn grammar online. Online grammar learning has significantly improved students' understanding of complex grammar concepts, confidence in using English, persuasive argument construction, and critical thinking skills.